2018
DOI: 10.1016/j.molmet.2018.02.008
|View full text |Cite
|
Sign up to set email alerts
|

GPR142 prompts glucagon-like Peptide-1 release from islets to improve β cell function

Abstract: ObjectiveGPR142 agonists are being pursued as novel diabetes therapies by virtue of their insulin secretagogue effects. But it is undetermined whether GPR142's functions in pancreatic islets are limited to regulating insulin secretion. The current study expands research on its action.Methods and ResultsWe demonstrated by in situ hybridization and immunostaining that GPR142 is expressed not only in β cells but also in a subset of α cells. Stimulation of GPR142 by a selective agonist increased glucagon secretion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 25 publications
3
22
1
Order By: Relevance
“…As expected, linagliptin did not increase active GLP-1 levels to control levels in the GcgRA ΔPDX1Cre mice as the pancreas is not a major contributor to circulating GLP-1. In line with previous reports [22][23][24], we believe pancreas-produced GLP-1 acts in a paracrine manner. In an important series of experiments, recent findings from a study using perifused islets demonstrated that both GLP-1 and glucagon secreted from alpha cells can act on beta cell GLP-1Rs to regulate insulin secretion [25].…”
Section: Discussionsupporting
confidence: 93%
“…As expected, linagliptin did not increase active GLP-1 levels to control levels in the GcgRA ΔPDX1Cre mice as the pancreas is not a major contributor to circulating GLP-1. In line with previous reports [22][23][24], we believe pancreas-produced GLP-1 acts in a paracrine manner. In an important series of experiments, recent findings from a study using perifused islets demonstrated that both GLP-1 and glucagon secreted from alpha cells can act on beta cell GLP-1Rs to regulate insulin secretion [25].…”
Section: Discussionsupporting
confidence: 93%
“…Silvestre et al 58 The amino acid sensor G-protein receptor 142 (GP142) could be also considered an orphan receptor that integrates anti-incretin activities, through stimulation of pancreatic glucagon secretion, but also exerts potent agonist actions on glucose disposal attaining a balance between insulin-mediated glucose uptake in fat and muscle and glucagon-mediated glucose production in the liver. 60 This effect could be considered as a physiological mechanism, designed to counteract or balance a possible incretin-induced hypoglycemia, or an anti-incretin compensatory response. Recent results by Rudenko et al 61 demonstrated that chronic treatment with a GP142 agonist in an obese mice model improved metabolic function, insulin sensitivity, and energy expenditure.…”
Section: Studies In Animalsmentioning
confidence: 99%
“…It also exerts potent agonist actions on glucose disposal attaining a balance between peripheral insulin-mediated glucose uptake and glucagon-mediated hepatic glycogenolysis. [60][61][62][63][64] Oxyntomodulin It affects insulin secretion via the GPCRs expressed by beta cells and increases glucose production through direct effects on hepatocytes. It also improves glucagon secretion in vitro and in vivo.…”
Section: -51mentioning
confidence: 99%
“…The main G protein-coupled receptors which activation appears to cause the release of GLP-1 are: GPRC6A ( 73 ), GPR40-41-42-43-93-119-120 ( 43 ), GPR142, GHS-R1A ( 74 ), Tas1R2-Tas2R3(T1R2-T1R3) ( 75 ), GPBAR1 (TGR5), and CasR ( 6 , 76 , 77 ) (Table 1 ). The functional differences seen between Jejunum-Ileal and colonic GLP-1 producing cells, could be explained by a different pool of GPCRs, or possibly by the presence of heteromers displaying a more complex pharmacology than with each individual receptor.…”
Section: Gpcrs As Molecular Tastantsmentioning
confidence: 99%
“…All of these receptors are expressed by pancreatic β cells, where their activation appears to mediate insulin release at low glucose levels and blockage at high levels ( 219 , 220 ), (see right side of Figure 2 ). On the other hand, INSL-5 targets a GPCR known as GPR142, also known as RXFP4, a receptor found to be expressed by the NCI-H716 cell line ( 54 ), and both α and β-cells in the pancreas, and its activation directly stimulates the expression of GLP-1 and insulin, representing a possible new pharmacological tool for the treatment of type 2 diabetes ( 77 , 221 ), and supporting a possible role for INSL-5 in the incretin effect. Xenin is another gut-derived food-induced peptide known to potentiate GIP activity ( 222 , 223 ).…”
Section: Expanding the Physiology Of Glp-1mentioning
confidence: 99%